2020
DOI: 10.1080/01612840.2020.1818014
|View full text |Cite
|
Sign up to set email alerts
|

EMDR in Telemental Health Counseling for Healthcare Workers Caring for COVID-19 Patients: A Pilot Study

Abstract: Background: The COVID-19 pandemic is putting a strain on health systems around the world. Healthcare workers, on the front lines of the epidemic, are facing major and potentially traumatic stressful events, overwhelming their ability to cope and their resources. Objective: The objective of this article will be to show how the use of the URG-EMDR protocol in a telemental health setting has proven to be feasible and effective in the treatment of a group of healthcare professionals working in nursing homes or hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 53 publications
(50 reference statements)
4
44
0
1
Order By: Relevance
“…Even if the intervention involved only one session, our findings are similar to those of previous research, which showed that even after a single session of EMDR, symptoms decreased significantly, effects of the intervention being constant after follow-up [ 32 , 33 , 34 , 35 , 36 , 37 ]. Moreover, this decrease in terms of symptoms was also found in other research where participants were treated remotely and the intervention was self-administered [ 3 , 38 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Even if the intervention involved only one session, our findings are similar to those of previous research, which showed that even after a single session of EMDR, symptoms decreased significantly, effects of the intervention being constant after follow-up [ 32 , 33 , 34 , 35 , 36 , 37 ]. Moreover, this decrease in terms of symptoms was also found in other research where participants were treated remotely and the intervention was self-administered [ 3 , 38 ].…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, one of the key findings of this study refers to the efficiency of such a system that offers the possibility of self-administration of an EMDR intervention, thus contributing to a limited body of research in this field [ 3 ]. Even if there are some developments and applications for EMDR therapy, the majority of the systems are not autonomous and require the permanent intervention of a clinician or are used only as a tool in treatment [ 38 , 42 ]. Compared to other systems, the unique advantages of the present system are as follows: The presence of an AI-driven chatbot, following the eight essential phases of EMDR [ 10 ], which can be further enhanced with new dialogue options and evaluation strategies; The ability to customize the interaction based on the patient’s characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Tarquinio et al [31] investigated the efficacy of a single EMDR session in reducing anxiety and depression levels as well as the perceived subjective level of disturbance. Seventeen nurses who were in treatment for non-Covid related issues in France had a single session of EMDR, through a video conferencing platform, using the URG-EMDR protocol [24].…”
Section: Online Emdrmentioning
confidence: 99%
“…Furthermore, there are doubts whether the implementation of EMDR via videoconference is feasible and appropriate ( Gibson et al, 2009 ; DPtV, 2020 ). As of now, there are only three studies which examined the effectiveness of internet-based EMDR ( Todder and Kaplan, 2007 ; Spence et al, 2013 ; Tarquinio et al, 2021 ). In the study of Tarquinio et al (2021) an adapted EMDR protocol was applied.…”
Section: Introductionmentioning
confidence: 99%
“…As of now, there are only three studies which examined the effectiveness of internet-based EMDR ( Todder and Kaplan, 2007 ; Spence et al, 2013 ; Tarquinio et al, 2021 ). In the study of Tarquinio et al (2021) an adapted EMDR protocol was applied. Healthcare providers suffering from the effects of the sanitary crisis in hospitals due to the COVID-19 pandemic were treated with the adapted protocol (URG-EMDR) via videoconference.…”
Section: Introductionmentioning
confidence: 99%